Configuration of Costomary Law Related to Economy (Economic Adat Law Study in North Sumatera, Indonesia) - Kamarusdiana Kamarusdiana; Mustapa Khamal Rokan (AHKAM : Jurnal Ilmu Syariah, 2018)
Tis paper wants to see the confguration of various forms ofcustomary law relating to the economy as a living law in society. Tis paperis based on research using qualitative methods with a historical approach.Te data was obtained from the feld and the interview which was thenprocessed analytically descriptive. Te results of this study obtained four (4)confgurations of customary law relating to the economy with the form, frst,the customary law of economic confguration of philanthropy in order touphold the teachings of religion (Islam) and habits found in society. Secondly,the confguration of semi-economic customary law in which businesses(capital owners) conduct business are accompanied to assist the farmers.Tird, the confguration of pure economic customary law in doing business.Fourth, the confguration of economic customary law in protecting nature.Tis research also strengthens socio-economic assumptions and impacts onthe social dimension in economic law.